2015
DOI: 10.1007/s12032-014-0329-5
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 expression in epithelial ovarian cancer: effect on cell EMT and clinical outcome

Abstract: Ras-related C3 botulinum toxin substrate 1 (rac1) has been implicated in tumor epithelial-mesenchymal transition (EMT); however, limited information is available regarding the role of rac1 in epithelial ovarian cancer (EOC). This study aimed to evaluate the correlation of rac1 expression with EMT and EOC prognosis. Rac1 protein levels of 150 EOC specimens were evaluated by immunohistochemical staining. Survival analysis was performed to determine the correlation between rac1 expression and survival. Cellular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 36 publications
11
52
1
Order By: Relevance
“…Rac1 is abnormally expressed and activated in stomach and ovarian cancers. The high expression of Rac1 is positively correlated with highly invasive cancer and poor prognosis 17, 18, 25. We found that Rac1 was significantly expressed in lung cancer tissues, and was positively correlated with TNM stage, metastasis and poor prognosis, which was consistent with Yuan K's report 26.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Rac1 is abnormally expressed and activated in stomach and ovarian cancers. The high expression of Rac1 is positively correlated with highly invasive cancer and poor prognosis 17, 18, 25. We found that Rac1 was significantly expressed in lung cancer tissues, and was positively correlated with TNM stage, metastasis and poor prognosis, which was consistent with Yuan K's report 26.…”
Section: Discussionsupporting
confidence: 90%
“…Reduced E-cadherin expression increases the expression of Vimentin, N-cadherin, Snail1, and Twist1. The study showed that high expression of Rac1 induced EMT in tumor cells in vitro and in vivo 17, 18, and promoted invasion and metastasis of tumor. The inhibition of Rac1 expression significantly up-regulated the expression of E-cadherin, down-regulated the expression of N-cadherin and Vimentin, and significantly inhibited EMT in cancer cells 21.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Z-scores were used to account for large differences in absolute GTPase activity levels observed for individual patient samples (Fig. 2C, 2D), likely related to known differences in GTPase overexpression seen in ovarian cancer (11, 12). The inhibitory effect of R-ketorolac in primary ovarian cancer cells is consistent with the observations in SKOV3ip cells.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ascites have been shown to enhance epithelial to mesenchymal transition (EMT) in ovarian cancer cells. 8,41,42 During EMT, a stationary epithelial cell transforms into a mesenchymal cell capable of motility. This transition is an important precursor for metastasis and chemoresistance.…”
Section: A the Ovarian Cancer Mechanical Microenvironmentmentioning
confidence: 99%